Analisis Peningkatan Perolehan Zakat di BAZNAS Jawa Timur Pascaterbitnya Surat Instruksi Gubernur Jawa Timur Tahun 2021 - Ubud, Nuril; Amrullah, Ahmad Afif; Afandi, Nihro (JES (Jurnal Ekonomi Syariah), 2024)
The Governor of East Java issued a letter of Instruction Number 01/INSTN/2021 concerning Optimizing the Collection of zakat, infaq and sadaqah within the East Java Provincial Government. This policy is a new breakthrough so that state civil servants (ASN) are aware of the obligation to pay zakat and increase the zakat income at the National Zakat Amil Agency (BAZNAS) East Java. In this way, the zakat funds collected can become a huge force that can be used to help improve the welfare of the poor, needy and the other zakat recipients. However, in fact, the issuance of this letter of instruction does not automatically become a determining factor in increasing the zakat collection of the BAZNAS East Java. This research uses a descriptive-qualitative method. Primary data was obtained by conducting direct interviews with the administrators and staff of BAZNAS East Java. Meanwhile, secondary data was obtained from literature, reference books, journals, documents and BAZNAS. In data analysis, researchers used inductive thinking to reach conclusions. The results of this research show that there has been a very significant increase after the issuance of the East Java Governor's Instruction letter number 01/INSTN/2021 regarding the optimization of zakat, infaq and sadaqah collection within the East Java Provincial government. However, to realize the effectiveness of implementing these instructions, BAZNAS East Java needs to carry out several follow-up programs as revealed in this research.